2012
DOI: 10.1249/mss.0b013e318249953c
|View full text |Cite
|
Sign up to set email alerts
|

Motor Unit Survival in Lifelong Runners Is Muscle Dependent

Abstract: Although there were no significant differences in MUNE between both older groups in the biceps brachii muscle, with the number of subjects tested here, we cannot eliminate the possibility of some whole-body neuroprotective effect. However, when compared with the remote biceps muscle, a greater influence on age-related spinal motoneuron survival was found in a chronically activated MN pool specific to the exercised muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 40 publications
5
86
0
2
Order By: Relevance
“…29 Similarly, it is reported that high levels of long-term physical activity can provide a maintenance of motor units in exercising muscle. 30 In the present study, estimated swim distance completed at a high intensity (Borg scale > 14) accounted for about 70% of total daily swim distance in high MS. In addition, swim fins are widely used for improving swim performance and have been associated with altering leg muscle activation during swim training sessions.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…29 Similarly, it is reported that high levels of long-term physical activity can provide a maintenance of motor units in exercising muscle. 30 In the present study, estimated swim distance completed at a high intensity (Borg scale > 14) accounted for about 70% of total daily swim distance in high MS. In addition, swim fins are widely used for improving swim performance and have been associated with altering leg muscle activation during swim training sessions.…”
Section: Discussionmentioning
confidence: 48%
“…34 A recent study demonstrated that the lifelong running can provide a localized maintenance of motor units in exercising muscle, but not systemically. 30 Thus, lifelong swimming exercise session with long distance (> 3000 meters) may prevent the site-specific muscle loss of the thigh.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that lifelong running can provide a localized maintenance of motor units in exercising muscle, but not systemically (Power et al 2012). Thus, changes in the intensity and/or duration of weight-bearing physical activity may be a main factor for decreasing anterior thigh MTH with age.…”
Section: Discussionmentioning
confidence: 99%
“…For decomposition-enhanced spike-triggered averaging (DE-STA) measures that include an estimate of the number of functional motor units (MUNE), intramuscular EMG signals were recorded via a disposable concentric needle electrode with a recording surface of 0.03 mm 2 (Model N53153; Teca, Hawthorne, New York) inserted into the TA, 5-10 mm proximal to the active surface electrode. The MUNE technique was performed similarly to what we have reported previously (Dalton et al 2008;McNeil et al 2005b;Power et al 2012aPower et al , 2010. Electromyography data were acquired using customized software on a Neuroscan Comperio system (Neurosoft, El Paso, Texas).…”
Section: Electrophysiological Propertiesmentioning
confidence: 99%